Paramagnetic effect of the magnetic field on superconductors with charge-density waves - Ekino, T.; Gabovich, A.M.; Voitenko, A.I. (Физика низких температур, 2005)
The limiting field Hp for spin-singlet superconductors with charge-density waves (CDWs),
which paramagnetically destroys the ordered phase, possessing coexisting superconducting and
CDW order parameters, is calculated self-consistently. It is shown that Hp always exceeds the
Pauli limits both for pure superconducting and pure CDW phases. Relevant experimental data for
inorganic and organic superconductors with high upper critical magnetic fields are analyzed and
are shown to be in qualitative agreement with the proposed theory.